Prévenir les conflits et promouvoir la coopération dans la gestion des fleuves transfrontaliers en Afrique de l’Ouest - Madiodio Niasse (VertigO)
The growing number of planned large dams, the high level of water interdependency among countries and the drastic reduction in water availability -in particular as a result of climate variability and change- have notably increased the risks of international water conflicts in West Africa. In such a context, the management of the region’s 25 transboundary watercourses is a real challenge. After having described some of the tensions and crises experienced in recent years, this article analyses the basin-level mechanisms for conflict management and for cooperation, with specific emphasis on the differences between boundary and transboundary river basin organization models. It also recalls some of the relevant provisions in international law and the emerging norms of good conduct in the management of shared watercourses. Finally, this articles makes key suggestions which would make transbounsary watercourses spaces for cooperation instead of fields of conflicts and tensions.